2017
DOI: 10.1186/s12898-017-0126-z
|View full text |Cite
|
Sign up to set email alerts
|

Propagule pressure increase and phylogenetic diversity decrease community’s susceptibility to invasion

Abstract: BackgroundInvasions pose a large threat to native species, but the question of why some species are more invasive, and some communities more prone to invasions than others, is far from solved. Using 10 different three-species bacterial communities, we tested experimentally if the phylogenetic relationships between an invader and a resident community and the propagule pressure affect invasion probability.ResultsWe found that greater diversity in phylogenetic distances between the members of resident community a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 24 publications
2
41
1
Order By: Relevance
“…Serratia marcescens ssp. marcescens (ATCC ® 13880™) was chosen as the invader because its ability to break DNA allowed easy recognition from other species using simple plating techniques (Ketola et al 2016 b, Ketola et al 2017). The 3 community species used in this study showed relatively high resistance against the invading S. marcescens , when reared together: Pseudomonas chlororaphis ATCC ® 17418™, Enterobacter aerogenes ATCC ® 13048™ and Leclercia adecarboxylata ATCC ® 23216™ (Ketola et al 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serratia marcescens ssp. marcescens (ATCC ® 13880™) was chosen as the invader because its ability to break DNA allowed easy recognition from other species using simple plating techniques (Ketola et al 2016 b, Ketola et al 2017). The 3 community species used in this study showed relatively high resistance against the invading S. marcescens , when reared together: Pseudomonas chlororaphis ATCC ® 17418™, Enterobacter aerogenes ATCC ® 13048™ and Leclercia adecarboxylata ATCC ® 23216™ (Ketola et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…We used a standard dilution series technique to achieve a 10 5 -fold dilution that allowed the counting of separate colonies on agar plates. We plated the samples on DNase test agar with methyl green (Becton and Dickinson and Company, Sparks, MD; premade at Tammer-tutkan maljat, Tampere, Finland) that enabled the separation of S. marcescens from the community species (see: Ketola et al 2016 b, Ketola et al 2017). The fate of specific community species was not monitored during the invasion experiment, due to frequent supplementation of species.…”
Section: Invasion Experimentsmentioning
confidence: 99%
“…In contrast to our hypothesis propagule pressure was less important than biotic interactions in driving variation in microbial composition and ecosystem functioning ( Figure 2). In both macro-and micro-organism studies increasing the number of invading individuals and the number of repeated introductions leads to higher invasion success in both field and laboratory experiments (10,15,20,21,39,48,49). Invasions with large numbers of diverse taxa compared to single taxa may increase the importance of biotic interactions relative to propagule pressure.…”
Section: Discussionmentioning
confidence: 99%
“…High phylogenetic diversity has been associated with a decrease in alien species abundance in an experimental plant community (Whitfeld et al 2014), as well as in natural plant communities (Iannone et al 2016, Ng et al 2019. Studying bacteria communities, Ketola et al (2017) found negative or no association between phylogenetic diversity and invasion success. So far, there are no empirical results of a positive association between phylogenetic diversity and the establishment or spread of alien species.…”
Section: Introductionmentioning
confidence: 98%
“…Studying bacteria communities, Ketola et al. () found negative or no association between phylogenetic diversity and invasion success. So far, there are no empirical results of a positive association between phylogenetic diversity and the establishment or spread of alien species.…”
Section: Introductionmentioning
confidence: 99%